2016
DOI: 10.3389/fnbeh.2016.00162
|View full text |Cite
|
Sign up to set email alerts
|

A Window on the Study of Aversive Instrumental Learning: Strains, Performance, Neuroendocrine, and Immunologic Systems

Abstract: The avoidance response is present in pathological anxiety and interferes with normal daily functions. The aim of this article is to shed light on performance markers of active avoidance (AA) using two different rat strains, Sprague-Dawley (SD) and Wistar. Specifically, good and poor performers were evaluated regarding anxiety traits exhibited in the elevated plus maze (EPM) and corticosterone levels and motor activity in the open field test. In addition, the plasma levels of Interleukin-6 (IL-6), Interleukin-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…In this test, the number of adaptive avoidance responses is scored along with the pattern of fear response exhibited to classify animals as presenting adaptive (AA) or maladaptive avoidance (MA) behaviour. Although this classification is commonly only established in the last two consecutive trials [ 3 , 4 , 18 ], behavioural differences between groups were observed since the first test and continued until the end of the experiment, suggesting that intrinsic differences between animals could determine a predisposition to develop maladaptive avoidance behaviour and exacerbated fear responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this test, the number of adaptive avoidance responses is scored along with the pattern of fear response exhibited to classify animals as presenting adaptive (AA) or maladaptive avoidance (MA) behaviour. Although this classification is commonly only established in the last two consecutive trials [ 3 , 4 , 18 ], behavioural differences between groups were observed since the first test and continued until the end of the experiment, suggesting that intrinsic differences between animals could determine a predisposition to develop maladaptive avoidance behaviour and exacerbated fear responses.…”
Section: Discussionmentioning
confidence: 99%
“…The test was performed as previously described [ 15 , 18 ]. Briefly, animals were tested 8 consecutive days (one 25-min session per day) in a two-way shuttle box placed inside a soundproof isolation cubicle (Insight Equipment, Brazil).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paradigm was performed as previously described [ 75 ]. In brief, animals were submitted to 25 min training sessions once a day for 8 consecutive days in a two-way shuttle box (Insight Equipment, Ribeirao Preto, Brazil).…”
Section: Methodsmentioning
confidence: 99%
“…Controls animals were exposed to the two-way shuttle box, but the footshock was turned off (i.e., without behavior contingency). Animals performing more than 20 avoidance responses in a session for 2 consecutive days were considered good performers, while animals that did not achieve this number were considered poor performers [ 7 , 75 , 76 ]. Freezing, defined as the absence of movement except that required for breathing [ 77 ], was assessed during the first 2 min of the tests [ 74 , 76 ].…”
Section: Methodsmentioning
confidence: 99%